A post-pandemic snapshot of the magnitude of COVID-19 in Brazil: A countrywide study - Eduardo Ribes Kohn; Maristela Bohlke; Antônia Almeida; Leandro Janelli; Luciana Monteiro Vasconcelos Sardinha; Fernando C. Wehrmeister; Pedro Curi Hallal (Brazilian Journal of Infectious Diseases)
Objective: To outline the features of COVID-19 in Brazil through a countrywide telephone survey. Methods: Data from the Telephone Survey of Risk Factors for Chronic Noncommunicable Diseases During the Pandemic (Covitel), a telephone survey of individuals aged 18 years or older from all macro-regions of Brazil, were used. The questionnaire included sociodemographic characteristics and outcomes related to COVID-19 infection, severity, vaccination, and use of masks. Results: Data revealed that 34.7 % (95 %CI 32.4 – 37.1) of the population had been diagnosed with COVID-19, and 10.1 % (95 %CI 7.9 – 12.7) of those required hospital admission. The prevalence of COVID-19 diagnosis increased with education level: <8 years (26.6 % [95 %CI 23.1 – 30.7]), 9–11 years (33.4 % [95 %CI 29.4 – 37.7]), and >11 years (53.2 % [95 % CI 49.7 – 56.8]). Nevertheless, the hospitalization rate of Brazilians with more than eleven years of education was lower (5.8 % [95 %CI 4.3 – 7.6]). In 2023, 92.9 % (95 %CI 90.9 – 94.4) of the Brazilian population was fully vaccinated against COVID-19, but only 37.2 % (95 %CI 33.5 – 40.9) have received the updated vaccinal scheme (two doses and two boosters). During the pandemic outbreak, 81.9 % (95 %CI 79.4 – 84.2) reported always using face masks. However, only 16.1 % (95 %CI 13.5 – 19.0) maintained this practice in 2023. Conclusion: There were inequalities in COVID-19 testing in Brazil. Testing and vaccination policies implemented in the COVID-19 pandemic must be reevaluated by the Brazilian government.